Evidence that post‐fire recovery of small mammals occurs primarily via in situ survival. (14th May 2021) - Hale, Susannah; Mendoza, Lorissa; Yeatman, Tom; Cooke, Raylene; Doherty, Tim; Nimmo, Dale; White, John G.
Abstract: Aim: As climate change intensifies and wildfire frequency and scale increase, it is critical we develop a robust understanding of how species recover from these major disturbances. Here, we aim to determine whether source populations for recovery following large‐scale intense wildfires are derived from either in situ survival, or immigration from surrounding unburnt areas (ex situ). Secondly, we sought to determine whether habitat elements (e.g., logs) within the landscape facilitate in situ survival of small mammals during fires. Location: Grampians National Park, south‐eastern Australia. Methods: We used long‐term post‐fire small mammal monitoring to investigate sources of recovery for small mammals, and camera trapping and habitat surveys immediately following large intense wildfires to assess evidence for and drivers of post‐fire survival. Results: We found no relationship between distance to unburnt vegetation and the occurrence of any native species, suggesting that in situ survival is the probable mechanism for recovery of post‐fire mammal populations, compared with immigration from external unburnt areas. We also show that key habitat elements such as rocks and large trees were associated with the occurrence of several species immediately post‐fire, suggesting a role for these features in facilitating the survival of species during and following fire. Main conclusions: We present evidence for post‐fire recovery being driven by in situ survival. In situ survival is facilitated by small unburnt patches and habitat elements in burnt areas. These surviving individuals become the founders for subsequent post‐fire population recovery. Given that globally we are seeing increasingly frequent large‐scale wildfires driven by climate change, the capacity for in situ survival will help mitigate some of the fire‐related impacts of climate change.